CDK4-mediated MnSOD activation and mitochondrial homeostasis in radioadaptive protection - Jin, Cuihong (Free Radic Biol Med, 2015)
Mammalian cells are able to sense environmental oxidative and genotoxic conditions such as the environmental low dose ionizing radiation (LDIR) present naturally on earth surface. The stressed cells then can induce a so-called radioadaptive response with an enhanced cellular homeostasis and repair capacity against subsequent similar genotoxic conditions such as a high dose radiation. MnSOD, a primary mitochondrial antioxidant in mammals, has long been known to play a crucial role in the radioadaptive protection through detoxifying O(2)·- generated by mitochondrial oxidative phosphorylation. Contrasted to the well-studied mechanisms of SOD2 gene regulation, the mechanisms underlying post-translational regulation of MnSOD for radioprotection remain to be defined. Herein, we demonstrate that Cyclin D1-cyclin-dependent kinase 4 (CDK4) serves as the messenger to deliver the stress signal to mitochondria to boost mitochondrial homeostasis in human skin keratinocytes under LDIR adaptive radioprotection. Cyclin D1/CDK4 is found to relocate to mitochondria at the same time as MnSOD enzymatic activation peaks without significant changes of total MnSOD protein level. The mitochondrial-localized CDK4 directly phosphorylates MnSOD at Serine 106 (S106), causing enhanced MnSOD enzymatic activity and mitochondrial respiration. Expression of mitochondria-targeted dominant negative CDK4 or the MnSOD-S106A mutant reverses LDIR-induced mitochondrial enhancement and adaptive protection. The CDK4-mediated MnSOD activation and mitochondrial metabolism boost are also detected in skin tissues of mice receiving in vivo whole body LDIR. These results demonstrate a unique CDK4-mediated mitochondrial communication that allows cells to sense environmental genotoxic stress and boost mitochondrial homeostasis via enhancing phosphorylation and activation of MnSOD.